(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Theatrical discourse is a reflection of reality and its variables and the meaning comes and is shaped by visions and fictional composition in order to shape a communication relationship with the recipient and find the meaning within its interpretation and reading with expectative abilities. Contemporary theatrical experience has been geared towards the observance of contemporary consciousness systems based on the prospects of reading, exemplary expectation and the fusion of the whole range of experiences within this space, constituting and resulting in clear experiences in the levels of text, presentation and receipt at the local, Arab and international levels